The science and simulation of human performance - Ness, James W.; Tepe, Victoria; Ritzer, Darren R. (Emerald, 2004)
Simulations are often used in the military and other performance-critical fields (e.g., law enforcement, aviation, emergency management) to assess readiness, to support training, management, and decision making and to conduct mission rehearsal. This volume documents the state of the art and presents a state of the possible individual and small unit human performance research and simulation. Distinguished scientists from within the military, academe, government and private industry consider how best to gather and relate human performance data, and offer specific recommendations to advance the development of models and simulations of individual and small unit behavior. The result is a uniquely interdisciplinary volume that draws upon the knowledge and experience of recognized experts whose insights converge upon problems of common interest and relevance to researchers, analysts, and developers.
Keywords: Psychology -- Applied Psychology.; Psychology -- Cognitive Psychology.; Intelligence & reasoning.; Performance technology.; Human engineering.; Cognitive science.; Human-machine systems.; elektronické knihy; electronic books